Fertilizer subsidies versus soil health payments: does policy incentives framing matter - Oyinbo, Oyakhilomen; Chamberlin, Jordan (CIMMYT, 2026)
Many fertilizer subsidy programs in Africa, characterized by limited flexibility, have produced smaller-than-expected overall returns, partly due to low and variable returns to fertilizer and limited uptake of complementary practices that can improve soil health and crop yield responses. Amid growing interest in repurposing fertilizer subsidies, whether more flexible policy incentives that allow farmers to invest in fertilizer and complementary inputs and practices locally relevant to their growing conditions and emphasizes soil health improvement can shape farmer behavior towards more sustainable cropping intensification remains underexplored. In this report, we provide ex-ante experimental evidence on how framing policy incentives conditions farmer valuation of soil health improvement and associated crop production outcomes in Zambia. We use datasets from a framed field experiment, enabling us to quantify and compare farmer valuations of soil health and other production attributes under two framings of policy incentives of equivalent monetary costs: 1) fertilizer subsidies, and 2) soil health payments. Our results demonstrate both immediate gains in the form of better yield outcomes and larger policy support, as well as longer-term gains, such as improvement in soil health are appealing attributes in smallholders’ maize-based cropping choices. However, we also find that higher yield risk and larger labor requirements are significant barriers that strongly shape their investment decisions. More importantly, we find that relative to the less flexible fertilizer subsidy policy framing, more flexible policy supports in the form of soil health payment framing substantially increase farmer valuations of soil health improvement and other cropping attributes. Notably, the observed effects are larger for soil health, and among men than women. Our findings underscore the importance of public investment in incentivizing farmer interest in soil health through policy programs, with greater flexibility and emphasis on soil health, beyond the narrow focus on inorganic fertilizer, which is a useful consideration for generating more value for money.